Tracheostomy in the Intensive Care Unit: a University Hospital in a Developing Country Study - El-Anwar,Mohammad Waheed (2017)
Abstract Introduction Tracheostomy is the commonest surgical procedure in intensive care units (ICUs). It not only provides stable airway and facilitates pulmonary toilet and ventilator weaning, but also decreases the direct laryngeal injury of endotracheal intubation, and improves patient comfort and daily living activity. Objective The objective of this study is to assess the incidence, indications, timing, complications (early and late), and the outcome of tracheostomy on patients in the intensive care units (ICU) at a university hospital in a developing country. Methods This study is an observational prospective study. It was performed at the otolaryngology department and ICU new surgery hospital on 124 ICU admitted patients. We collected patients' demographic records, cause of admission, indications of tracheostomy, mechanical ventilation, and duration of ICU stay. We also gathered patientś tracheostomy records including the incidence, timing, technique, type, early and late complications, and outcome. All tracheostomized patients received follow-up for 12 months. Results The indication for tracheostomy in ICU patients was mostly prolonged intubation (80.5%), followed by diaphragmatic paralysis (19.5%). All tracheostomies were done by the open approach technique. Tracheostomy for prolonged intubation was done within 17 to 26 days after intubation with a mean of 19.4 ± 2.07 days. Complications after tracheostomy were 13.9% tracheal stenosis and 25% subglottic stenosis. Conclusion Prolonged endotracheal intubation is theman indication of tracheostomy, performed after two weeks of intubation. Although there were no major early complications, laryngotracheal stenosis is still a challenging sequel for tracheostomy that needs to be investigated to be prevented.